High-activity high-temperature-resistant methanol catalyst and preparation method thereof

CN122230708BActive Publication Date: 2026-10-16XIANGTAN ELECTROCHEMICAL SCI CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610686406.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-19
Publication Date
2026-10-16
Estimated Expiration
2046-05-19

AI Technical Summary

Technical Problem

但是在高温反应条件下,活性金属铜纳米颗粒容易发生烧结现象,导致催化剂活性位点减少,催化性能下降;同时,虽然ZnO可以在一定程度上稳定Cu颗粒,但在长期反应过程中,活性位点(如Cu-ZnO界面)会发生结构演变或被反应产物覆盖,影响催化活性;此外,Al2O3虽然提高了催化剂的比表面积,有助于反应过程中Cu活性位点的暴露,但是在高温反应条件下,Al2O3载体会发生相变或结构坍塌,导致比表面积下降、活性组分颗粒团聚、活性位点流失,影响催化剂的长期稳定性

Benefits of technology

本发明的催化剂通过构建独特的“氧化铜-氧化锌为核、锌-氧-铝复合氧化物为中间层、氧化铝为壳”的三明治结构,实现了活性组分与载体的协同作用。核层的氧化铜-氧化锌作为主要活性中心,为甲醇合成反应提供了丰富的活性位点;中间层的锌-氧-铝复合氧化物不仅自身具有一定的催化活性,更重要的是其作为核与壳之间的过渡层,能够有效抑制核层活性金属颗粒在高温下的迁移和烧结,同时增强了核与壳层之间的相互作用,提高了催化剂结构的整体稳定性;壳层的氧化铝则为整个催化剂提供了良好的机械强度和热稳定性,有效保护了内部活性结构在高温反应环境下免受破坏。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122230708B_ABST
    Figure CN122230708B_ABST
Patent Text Reader

Abstract

The application provides a high-activity high-temperature-resistant methanol catalyst and a preparation method thereof, and belongs to the technical field of catalysts. The catalyst has a sandwich structure with copper oxide-zinc oxide as a core, zinc-oxygen-aluminum composite oxide as an intermediate layer, and aluminum oxide as a shell. The catalyst contains a doping element. The doping element includes a first doping element for regulating an active component and a second doping element for modifying a carrier. The first doping element is distributed in the core and is selected from at least one of alkaline earth metals. The second doping element is distributed in the shell and is selected from at least one of rare earth metals and d-block metals. The application significantly improves the number of active centers, dispersion and structural stability of the catalyst by introducing specific additives and using a step-by-step precipitation method to construct a sandwich structure, thereby exhibiting more excellent catalytic performance and high-temperature resistance in a methanol synthesis reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of catalyst technology, and in particular to a highly active, high-temperature resistant methanol catalyst and its preparation method. Background Technology

[0002] Among numerous carbon conversion products, methanol is known as "liquid sunshine." It serves as both a fuel (direct combustion / fuel cell) and a fundamental chemical feedstock (MTO→olefins, MTP→propylene), with a wide range of applications. Industrially, methanol is typically produced from syngas containing H2, CO, and CO2 under specific pressure, temperature, and catalyst conditions. Therefore, the research and development of methanol catalysts is crucial for the development of the methanol industry.

[0003] For catalysts used in the synthesis of methanol from syngas, copper-based catalysts are commonly used industrially. Through continuous improvement and development, copper-based catalysts are mainly divided into Cu-Zn-Al and Cu-Zn-Zr systems. Currently, medium- and low-pressure gas-phase methods are widely used for methanol synthesis worldwide, and commercially available methanol catalysts are primarily mixed oxides of copper, zinc, and aluminum. In Cu / ZnO / Al₂O₃ catalysts, the addition of ZnO allows the catalyst to form a ZnO-CuO solid solution, significantly improving the catalyst's activity and selectivity. Al₂O₃ acts as a support in the catalyst, increasing its specific surface area and the dispersion of the active copper component.

[0004] Currently, the typical reaction conditions for methanol production using Cu / ZnO / Al₂O₃ catalysts are between 200–300°C and 5–10 MPa (50–100 bar), requiring long-term operation. However, under high-temperature reaction conditions, active copper nanoparticles are prone to sintering, leading to a reduction in active sites and a decline in catalytic performance. Simultaneously, although ZnO can stabilize Cu particles to some extent, active sites (such as the Cu-ZnO interface) undergo structural evolution or are covered by reaction products during long-term reactions, affecting catalytic activity. Furthermore, while Al₂O₃ increases the specific surface area of ​​the catalyst, facilitating the exposure of Cu active sites during the reaction, the Al₂O₃ support undergoes phase transitions or structural collapse under high-temperature conditions, resulting in a decrease in specific surface area, agglomeration of active components, and loss of active sites, impacting the long-term stability of the catalyst. Therefore, how to prepare highly active catalysts while simultaneously improving their high-temperature resistance remains a pressing issue. Summary of the Invention

[0005] This application addresses the aforementioned problems and aims to provide a highly active, high-temperature resistant methanol catalyst and its preparation method. The catalyst of this invention possesses a CuO-ZnO / Zn-O-Al / Al2O3 sandwich structure. Furthermore, the active material is modified by doping with alkaline earth metals (such as Ca, Mg, Ba, etc.) to further improve the dispersibility of the active metal copper and the auxiliary agent zinc, as well as the surface pH of the catalyst, thereby enhancing its adsorption of H2 and CO molecules. The Zn-O-Al bond provides certain catalytic activity while improving the catalyst's anti-sintering performance. Additionally, the support (Al2O3) is modified with rare earth metals (such as Ce, La, Pr, etc.) and d-block metals (such as Mn, Zr, Ti, etc.) to further improve the catalyst's anti-sintering properties.

[0006] Specifically, the first aspect of this application provides a highly active, high-temperature resistant methanol catalyst, which has a sandwich structure with copper oxide-zinc oxide as the core, zinc-oxygen-aluminum composite oxide as the intermediate layer, and alumina as the shell.

[0007] Furthermore, the catalyst contains doping elements; the doping elements include a first doping element for regulating the active component and a second doping element for modifying the support.

[0008] Furthermore, the first dopant element is distributed in the core and is selected from at least one of the alkaline earth metals Ca, Mg, and Ba; the second dopant element is distributed in the shell and is selected from at least one of the rare earth metals Ce, La, and Pr and the d-block metals Mn, Zr, and Ti.

[0009] Furthermore, based on the total mass of the catalyst, the catalyst comprises the following components in parts by mass: 52-74 parts copper oxide, 17-27 parts zinc oxide, 9-23 parts aluminum oxide, 0.5-2 parts alkaline earth metal oxides, and 1-5 parts rare earth metal oxides or d-zone metal oxides.

[0010] The second aspect of this application provides a method for preparing a highly active, high-temperature resistant methanol catalyst, comprising the following steps: Prepare at least three different metal salt solutions, which are respectively used to form the core, intermediate layer and shell of the catalyst; By using a stepwise coprecipitation method, under first conditions, a first metal salt solution used to form the core is reacted with a portion of a first precipitant to obtain a core slurry; Under the second condition, a second metal salt solution for forming the intermediate layer and a second precipitant are added to the core slurry and precipitated on the surface of the solid particles of the core slurry to obtain a first precipitated slurry; The third metal salt solution used to form the shell is reacted with another portion of the first precipitant to obtain a second precipitate slurry; The first precipitated slurry and the second precipitated slurry are mixed and then aged. The aged product was subjected to solid-liquid separation, washing, drying, and calcination to obtain the catalyst precursor; The catalyst precursor is shaped to obtain the methanol catalyst.

[0011] Furthermore, the first metal salt solution is a mixed aqueous solution containing zinc salt, copper salt and a first doping element salt; The second metal salt solution is a mixed aqueous solution containing zinc salt and aluminum salt; The third metal salt solution is a mixed aqueous solution containing aluminum salt and a second doped element salt.

[0012] Furthermore, the first precipitant is a carbonate solution, preferably a sodium carbonate solution; The second precipitant is a mixed solution of carbonate and alkali metal hydroxide, preferably a mixed solution of sodium carbonate and sodium hydroxide.

[0013] Furthermore, the molar ratio of zinc to aluminum in the second metal salt solution is 1.5-2.5:1; and the molar ratio of sodium carbonate to sodium hydroxide in the second precipitant is 1-3:1.

[0014] Furthermore, the first conditions include: a reaction temperature of 60-80°C, a reaction pH value maintained at 6.5-7.5, and an aging time of 1-3 hours; The second condition includes: a reaction temperature of 60-80℃, a reaction pH value maintained at 8.5-9.5, and an aging time of 0.5-2 hours.

[0015] Furthermore, the temperature of the roasting step is 300-400℃, and the roasting time is 3-6 hours.

[0016] Furthermore, the molding step includes adding graphite to the calcined catalyst precursor and pressing it into tablets, wherein the amount of graphite added is 1-3 wt% of the total mass of the catalyst.

[0017] The present invention has the following beneficial effects: The catalyst of this invention achieves synergistic effects between the active components and the support by constructing a unique sandwich structure of "copper oxide-zinc oxide as the core, zinc-oxygen-aluminum composite oxide as the intermediate layer, and alumina as the shell." The copper oxide-zinc oxide core layer serves as the main active center, providing abundant active sites for the methanol synthesis reaction. The zinc-oxygen-aluminum composite oxide in the intermediate layer not only possesses certain catalytic activity itself, but more importantly, as a transition layer between the core and shell, it effectively inhibits the migration and sintering of the active metal particles in the core layer at high temperatures, while simultaneously enhancing the interaction between the core and shell layers and improving the overall stability of the catalyst structure. The alumina in the shell layer provides the entire catalyst with good mechanical strength and thermal stability, effectively protecting the internal active structure from damage under high-temperature reaction conditions.

[0018] Furthermore, by introducing a first dopant element (alkaline earth metal) to regulate the active components of the core layer, the dispersion of active copper can be further improved, and the pH of the catalyst surface can be optimized, thereby enhancing its adsorption and activation capabilities for H2 and CO molecules and improving catalytic activity. Meanwhile, the second dopant elements (rare earth metals and d-block metals) distributed in the shell layer effectively modify the alumina support, further enhancing its thermal stability and anti-sintering properties, and delaying phase transformation or structural collapse during long-term high-temperature operation.

[0019] This invention significantly improves the number, dispersion, and structural stability of the catalyst by optimizing the ratio of active components, introducing specific additives, and using a stepwise precipitation method to construct a "sandwich" structure, thereby exhibiting superior catalytic performance and high-temperature tolerance in the methanol synthesis reaction. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of this drawing or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this drawing. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0021] Figure 1 The image shows the SEM pattern of ZnAl2O4 in the sample of Example 1. Figure 2 The image shows the SEM image of the CuO-ZnO / Zn-O-Al / Al2O3 sandwich structure in the sample of Example 1. Figure 3 The XRD patterns of the samples prepared for the examples and comparative examples after calcination are shown.

[0022] The purpose, features, and advantages of this accompanying drawing will be further explained in conjunction with the embodiments and with reference to the accompanying drawing. Detailed Implementation

[0023] To make the objectives, technical solutions, and advantages of this application clearer, the following description and illustration are provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application. All other embodiments obtained by those skilled in the art based on the embodiments provided in this application without inventive effort are within the scope of protection of this application.

[0024] Obviously, the following description is merely some examples or embodiments of this application. Those skilled in the art can apply this application to other similar scenarios without any inventive effort. Furthermore, it is understood that although the effort involved in such development may be complex and lengthy, for those skilled in the art related to the content disclosed in this application, any changes to design, manufacturing, or production based on the technical content disclosed in this application are merely conventional technical means and should not be construed as insufficient disclosure of the content of this application.

[0025] An embodiment of the first aspect of this application provides a highly active, high-temperature resistant methanol catalyst, the catalyst having a sandwich structure with copper oxide-zinc oxide as the core, zinc-oxygen-aluminum composite oxide as the intermediate layer, and alumina as the shell.

[0026] The sandwich structure of the catalyst is the core design of this invention, enabling a synergistic improvement in both high activity and high-temperature resistance. The core layer, composed of copper oxide and zinc oxide, serves as the main active center for the catalytic reaction. Its highly dispersed copper species provide abundant active sites for methanol synthesis, while the zinc oxide not only forms a highly active CuO-ZnO interface with copper but also disperses and stabilizes the copper particles. The intermediate zinc-oxygen-aluminum composite oxide (Zn-O-Al) layer is not simply a physical isolation layer but tightly connects the core and shell layers through chemical bonding. This structure, on the one hand, utilizes the characteristics of the Zn-O-Al bond to enhance the overall thermal stability of the catalyst, effectively preventing the migration and aggregation of copper particles in the core layer at high temperatures; on the other hand, the composite oxide itself may also participate in the catalytic reaction or further optimize the reaction pathway by modulating the electronic environment and surface properties of the catalyst. The alumina shell layer provides solid structural support for the entire catalyst. Its good mechanical strength and chemical inertness ensure the structural integrity of the catalyst under industrial reaction conditions, while its porous nature also facilitates the diffusion and mass transfer of reactant gases.

[0027] In this embodiment, the catalyst contains doping elements; the doping elements include a first doping element for regulating the active component and a second doping element for modifying the support. Preferably, the first doping element is distributed in the core and is selected from at least one alkaline earth metal; the second doping element is distributed in the shell and is selected from at least one rare earth metal and / or d-block metal.

[0028] This application further optimizes catalyst performance through the precise distribution and synergistic effect of dopant elements. The first dopant element (alkaline earth metals, such as Ca, Mg, Ba, etc.) is selectively distributed in the core layer, improving the dispersion of copper and zinc and preventing sintering at high temperatures. Simultaneously, the introduction of alkaline earth metals can regulate the pH of the catalyst surface, increasing the number of alkaline sites, which is crucial for the adsorption and activation of CO molecules, as CO adsorption typically requires an alkaline environment. The second dopant element (rare earth metals such as Ce, La, Pr, and d-block metals such as Mn, Zr, Ti, etc.) is mainly distributed in the alumina shell. The doping of these elements effectively inhibits grain growth and phase transformation of the alumina support at high temperatures, maintaining the support's high specific surface area and porous structure. Rare earth metals typically possess abundant oxygen vacancies and good oxygen storage capacity, enhancing the redox performance of the support and potentially assisting in the removal of carbon deposits or reactive oxygen species during the reaction process, thereby protecting the active sites. d-block metals such as Zr and Ti can form stable solid solutions or composite oxides with alumina, which can significantly improve the thermal stability and mechanical strength of the carrier and delay its structural collapse.

[0029] In this embodiment, the catalyst comprises the following components by mass: 52-74 parts copper oxide, 17-27 parts zinc oxide, 9-23 parts aluminum oxide, 0.5-2 parts alkaline earth metal, and 1-5 parts rare earth metal or d-block metal.

[0030] The second aspect of this application provides a method for preparing a highly active, high-temperature resistant methanol catalyst, comprising the following steps: Prepare at least three different metal salt solutions, which are respectively used to form the core, intermediate layer and shell of the catalyst; By using a stepwise coprecipitation method, under first conditions, a first metal salt solution used to form the core is reacted with a portion of a first precipitant to obtain a core slurry; Under the second condition, a second metal salt solution for forming the intermediate layer and a second precipitant are added to the core slurry and precipitated on the surface of the solid particles of the core slurry to obtain a first precipitated slurry; The third metal salt solution used to form the shell is reacted with another portion of the first precipitant to obtain a second precipitate slurry; The first precipitated slurry and the second precipitated slurry are mixed and then aged. The aged product was subjected to solid-liquid separation, washing, drying, and calcination to obtain the catalyst precursor; The catalyst precursor is shaped to obtain the methanol catalyst.

[0031] Furthermore, the first metal salt solution is a mixed aqueous solution containing zinc salt, copper salt, and optionally a first dopant element salt; The second metal salt solution is a mixed aqueous solution containing zinc salt and aluminum salt; The third metal salt solution is a mixed aqueous solution containing aluminum salt and optionally a second doping element salt.

[0032] Preferably, a mixed aqueous solution of zinc, copper and additives (Mg, Ca, Ba, etc.) nitrates is prepared, denoted as the first metal salt solution; a mixed aqueous solution of zinc and aluminum nitrates is prepared, denoted as the second metal salt solution; and a mixed aqueous solution of aluminum and additives (Mn, Zr, Ti, Ce, La, Pr, etc.) nitrates is prepared, denoted as the third metal salt solution.

[0033] Furthermore, the first precipitant is a carbonate solution, preferably a sodium carbonate solution; the second precipitant is a mixed solution of carbonate and alkali metal hydroxide, preferably a mixed solution of sodium carbonate and sodium hydroxide.

[0034] Preferably, a Na2CO3 solution is prepared and designated as the first precipitant; a mixed solution of Na2CO3 and NaOH is prepared and designated as the second precipitant.

[0035] Add an appropriate amount of deionized water as a base solution to the first reactor. Then, add the first metal salt solution and the first precipitant dropwise into the reactor while stirring at a uniform speed. Adjust the reaction temperature in the reactor to 60-80℃ and the pH of the precipitate to 6.5-7.5, maintaining them within a suitable range. After the first metal salt solution has been added dropwise, stop adding the first precipitant and continue stirring and aging for 1-3 hours to obtain the core slurry. Then, add the second metal salt solution and the second precipitant in the same manner, adjusting the reaction temperature in the reactor to 60-80℃ and the pH of the precipitate to 8.5-9.5, maintaining them within a suitable range. After the second metal salt solution has been added dropwise, stop adding the first precipitant and continue stirring and aging for 1-3 hours to obtain the core slurry. After the metal salt solution is added dropwise, the addition of the second precipitant is stopped, and the mixture is aged in the reactor for 0.5-2 hours to obtain the first precipitate slurry. Then, the third metal salt solution and another portion of the first precipitant are added to the second reactor in the same manner, and the reaction temperature in the reactor is adjusted to 60-80℃, and the pH value of the precipitate is maintained at 7.0-8.5, keeping it within a suitable range. After the third metal salt solution is added dropwise, the addition of the second precipitant is stopped, and the mixture is aged in the reactor for 10-30 minutes to obtain the second precipitate slurry. Subsequently, the first precipitate slurry and the second precipitate slurry are mixed and aged under a certain speed for 0.5-2 hours.

[0036] In the above steps, the reaction temperature of the second metal salt solution and the second precipitant is 60-80℃. If the temperature is too low, a thick Zn-O-Al layer is easily formed, burying the active sites and reducing the activity of the catalyst. If the temperature is too high, a small-particle Zn-O-Al layer is easily formed, failing to achieve the coating effect. The reaction pH is maintained at 8.5-9.5. The precipitate in the first precipitation slurry is zinc malachite, which exhibits a certain alkalinity on its surface. Therefore, during the dropwise addition, zinc and aluminum ions will preferentially precipitate on the precipitate surface. However, if the pH is too low, Zn and Al will precipitate as Al(OH)3 and Zn5(CO3)2•6H2O respectively, and zinc-aluminum hydrotalcite cannot be formed, resulting in the inability to form a Zn-O-Al layer after subsequent calcination. If the pH is too high, Zn and Al will precipitate in the solution and cannot precipitate on the precipitate surface in the first precipitation slurry, failing to achieve the coating effect. Therefore, the reaction pH must be strictly controlled during the dropwise addition. The aging time is 0.5-2 hours. If the aging time is too short, the Zn-O-Al layer particles will be too small and will not achieve a good high temperature resistance effect. If the aging time is too long, the Zn-O-Al layer particles will be too large and will bury the active sites, thus reducing the catalyst activity.

[0037] In this embodiment, the molar ratio of zinc to aluminum in the second metal salt solution is 1.5-2.5:1; and the molar ratio of sodium carbonate to sodium hydroxide in the second precipitant is 1-3:1.

[0038] In this embodiment, the temperature of the roasting step is 300-400℃, and the roasting time is 3-6 hours.

[0039] In this embodiment, the molding step includes adding graphite to the calcined catalyst precursor and pressing it into tablets, wherein the amount of graphite added is 1-3 wt% of the total mass of the catalyst.

[0040] This invention constructs a CuO-ZnO / Zn-O-Al / Al2O3 sandwich structure, with the Zn-O-Al layer located between the active layer and the support layer. This effectively improves the dispersion of the active components and also serves as a partial support, enhancing the catalyst's resistance to sintering. Furthermore, to further improve catalyst activity, this invention modifies the catalyst active layer (Cu / ZnO) with alkaline earth metals, promoting the formation of effective precursors, further reducing the defect level in the ZnO structure, effectively enhancing the interaction between the Cu and ZnO interfaces, and thus improving catalyst activity. Simultaneously, to further improve the material's resistance to sintering, this invention uses d-block metals and rare earth metals to dope and modify the support (Al2O3), effectively improving the catalyst's high-temperature activity and stability.

[0041] Example The following examples describe the disclosure of this invention in more detail. These examples are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of this disclosure. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on weight. Unless otherwise stated, all reagents used in the examples are available commercially or synthesized using conventional methods and are ready for use without further processing. Unless otherwise stated, all instruments used in the examples are available commercially.

[0042] Example 1 Weigh 278.52g Cu(NO3)2·3H2O, 80.30g Zn(NO3)2·6H2O, and 10.77g Mg(NO3)3·6H2O, dissolve them in 1500ml deionized water, and stir until completely dissolved to obtain the first metal salt solution. Weigh 22.92g Zn(NO3)2·6H2O and 57.78g Al(NO3)3·9H2O, dissolve them in 230ml deionized water, and stir until completely dissolved to obtain the second metal salt solution. Weigh 57.78g Al(NO3)3·9H2O and 6.95g Ce(NO3)3·6H2O, dissolve them in 154mL deionized water, and stir until completely dissolved to obtain the third metal salt solution. Weigh 265.00g Na2CO3, dissolve it in 2500ml deionized water, and stir until completely dissolved to obtain the first precipitant. Weigh 79.50g Na2CO3 and 10.00g NaOH and dissolve them in 1000ml deionized water, stirring until completely dissolved to obtain the second precipitant; The first metal salt solution and a portion of the first precipitant were added dropwise to the first reactor in a parallel flow. The mixture was continuously stirred throughout the process, and the pH value was controlled between 6.5 and 7.0 by adjusting the feed rates of the salt and alkali. The water bath temperature was maintained at 70°C. Once all the first metal salt solution had been added, the addition of the first precipitant was stopped. Stirring continued for 1 hour, with the stirrer running continuously. Then, the second metal salt solution was added in the same manner, while the second precipitant was added dropwise. Throughout this process, the pH value was controlled between 8.5 and 9.5 by adjusting the feed rates of the salt and alkali, and the water bath temperature was maintained at 70°C. Once all the second metal salt solution had been added to the reactor, the addition of the second precipitant was stopped, and the precipitate was allowed to age at a constant temperature in the reactor for 2 hours to obtain the first precipitate slurry.

[0043] The third metal salt solution and another portion of the first precipitant were then added dropwise to the second reactor in a parallel flow. Throughout the process, the mixture was continuously stirred, and the pH was controlled between 7.5 and 8.5 by adjusting the feed rates of the salt and alkali. The water bath temperature was maintained at 70°C. Once the third metal salt solution had been completely added, the addition of the first precipitant was stopped. Stirring continued for 30 minutes to obtain the second precipitate slurry.

[0044] Finally, the first and second precipitated slurries were mixed and stirred for another 2 hours. Afterward, the mixture was filtered, washed with deionized water, and filtered again. This process was repeated until no Na was detected. + The filter cake was dried and crushed, and the dried material was calcined at 350℃ for 6 hours to decompose it, obtaining calcined powder. The calcined powder was then mixed with 2wt% graphite to form a methanol synthesis catalyst sample 1.

[0045] The mass percentages of sample 1 are as follows: CuO: 60.8%, ZnO: 23.5%, Al2O3: 11.7%, MgO: 1.5%, CeO2: 2.5%.

[0046] SEM images of ZnAl2O4 in the sample are shown below. Figure 1 The SEM images of the CuO-ZnO / Zn-O-Al / Al2O3 sandwich structure in the sample are shown below. Figure 2 .

[0047] Example 2 Weigh 279.90g Cu(NO3)2·3H2O, 76.50g Zn(NO3)2·6H2O, and 10.77g Mg(NO3)3·6H2O, dissolve them in 1500ml deionized water, and stir until completely dissolved to obtain the first metal salt solution. Weigh 24.90g Zn(NO3)2·6H2O and 52.52g Al(NO3)3·9H2O, dissolve them in 230ml deionized water, and stir until completely dissolved to obtain the second metal salt solution. Weigh 57.78g Al(NO3)3·9H2O and 7.14g Zr(NO3)2·5H2O, dissolve them in 154mL deionized water, and stir until completely dissolved to obtain the third metal salt solution. Weigh 265.00g Na2CO3, dissolve it in 2500ml deionized water, and stir until completely dissolved to obtain the first precipitant. Weigh 79.50g Na2CO3 and 10.00g NaOH and dissolve them in 1000ml deionized water, stirring until completely dissolved to obtain the second precipitant; The first metal salt solution and the first precipitant were added dropwise to the first reactor in a parallel flow, with continuous stirring throughout the process. The pH value was controlled between 6.5 and 7.5 by adjusting the feed rates of the salt and alkali, and the water bath temperature was maintained at 70°C. Once all the first metal salt solution had been added, the addition of the first precipitant was stopped. Stirring continued for 2 hours without stopping. Then, the second metal salt solution was added in the same manner, while the second precipitant was added dropwise. Throughout this process, the pH value was controlled between 8.5 and 9.5 by adjusting the feed rates of the salt and alkali, and the water bath temperature was maintained at 70°C. Once all the second metal salt solution had been added to the reactor, the addition of the second precipitant was stopped, and the precipitate was allowed to age at a constant temperature in the reactor for 1 hour to obtain the first precipitate slurry.

[0048] The third metal salt solution and another portion of the first precipitant were then added dropwise to the second reactor in a parallel flow. Throughout the process, the mixture was continuously stirred, and the pH was controlled between 7.5 and 8.5 by adjusting the feed rates of the salt and alkali. The water bath temperature was maintained at 70°C. Once the third metal salt solution had been completely added, the addition of the first precipitant was stopped. Stirring continued for 30 minutes to obtain the second precipitate slurry.

[0049] Finally, the first and second precipitated slurries were mixed and stirred for another 2 hours. Afterward, the mixture was filtered, washed with deionized water, and filtered again. This process was repeated until no Na was detected. + The filter cake was dried and crushed, and the dried material was calcined at 400℃ for 2 hours to decompose it, obtaining calcined powder. The calcined powder was then mixed with 2wt% graphite to form a methanol synthesis catalyst sample 2.

[0050] The mass percentages of sample 2 are as follows: CuO: 62.3%, ZnO: 22.5%, Al2O3: 11.5%, MgO: 1.5%, ZrO2: 2.2%.

[0051] Example 3 Weigh 279.90g Cu(NO3)2·3H2O, 76.50g Zn(NO3)2·6H2O, and 12.56g Ca(NO3)2·4H2O, dissolve them in 1500ml deionized water, and stir until completely dissolved to obtain the first metal salt solution. Weigh 24.90g Zn(NO3)2·6H2O and 52.52g Al(NO3)3·9H2O, dissolve them in 230ml deionized water, and stir until completely dissolved to obtain the second metal salt solution. Weigh 57.78g Al(NO3)3·9H2O and 8.29g Mn(NO3)2·4H2O, dissolve them in 154mL deionized water, and stir until completely dissolved to obtain the third metal salt solution. Weigh 265.00g Na2CO3, dissolve it in 2500ml deionized water, and stir until completely dissolved to obtain the first precipitant. Weigh 79.50g Na2CO3 and 10.00g NaOH and dissolve them in 1000ml deionized water, stirring until completely dissolved to obtain the second precipitant; The first metal salt solution and the first precipitant were added dropwise to the first reactor in a parallel flow, with continuous stirring throughout the process. The pH value was controlled between 6.5 and 7.5 by adjusting the feed rates of the salt and alkali, and the water bath temperature was maintained at 70°C. Once all the first metal salt solution had been added, the addition of the first precipitant was stopped. Stirring continued for 2 hours without stopping. Then, the second metal salt solution was added in the same manner, while the second precipitant was added dropwise. Throughout this process, the pH value was controlled between 8.5 and 9.5 by adjusting the feed rates of the salt and alkali, and the water bath temperature was maintained at 70°C. Once all the second metal salt solution had been added to the reactor, the addition of the second precipitant was stopped, and the precipitate was allowed to age at a constant temperature in the reactor for 1 hour to obtain the first precipitate slurry.

[0052] The third metal salt solution and another portion of the first precipitant were then added dropwise to the second reactor in a parallel flow. Throughout the process, the mixture was continuously stirred, and the pH was controlled between 7.5 and 8.5 by adjusting the feed rates of the salt and alkali. The water bath temperature was maintained at 70°C. Once the third metal salt solution had been completely added, the addition of the first precipitant was stopped. Stirring continued for 30 minutes to obtain the second precipitate slurry.

[0053] Finally, the first and second precipitated slurries were mixed and stirred for another 2 hours. Afterward, the mixture was filtered, washed with deionized water, and filtered again. This process was repeated until no Na was detected. + The filter cake was dried and crushed, and the dried material was calcined at 350℃ for 5 hours to decompose it, obtaining calcined powder. The calcined powder was then mixed with 2wt% graphite to form a methanol synthesis catalyst sample 3.

[0054] The mass percentages of sample 3 are as follows: CuO: 61.8%, ZnO: 23.0%, Al2O3: 11.5%, CaO: 1.5%, MnO2: 2.2%.

[0055] Comparative Example 1 Weigh 278.52g Cu(NO3)2·3H2O and 80.30g Zn(NO3)2·6H2O, dissolve them in 1500ml deionized water, and stir until completely dissolved to obtain the first metal salt solution. Weigh 22.92g Zn(NO3)2·6H2O and 57.78g Al(NO3)3·9H2O, dissolve them in 230ml deionized water, and stir until completely dissolved to obtain the second metal salt solution. Weigh 57.78g Al(NO3)3·9H2O, dissolve it in 154mL deionized water, and stir until completely dissolved to obtain the third metal salt solution. Weigh 265.00g Na2CO3, dissolve it in 2500ml deionized water, and stir until completely dissolved to obtain the first precipitant. Weigh 79.50g Na2CO3 and 10.00g NaOH and dissolve them in 1000ml deionized water, stirring until completely dissolved to obtain the second precipitant; The first metal salt solution and the first precipitant were added dropwise to the first reactor in a parallel flow, with continuous stirring throughout the process. The pH value was controlled between 6.5 and 7.0 by adjusting the feed rates of the salt and alkali, and the water bath temperature was maintained at 70°C. Once all the first metal salt solution had been added, the addition of the first precipitant was stopped. Stirring continued for 2 hours without stopping. Then, the second metal salt solution was added in the same manner, while the second precipitant was added dropwise. Throughout this process, the pH value was controlled between 8.5 and 9.5 by adjusting the feed rates of the salt and alkali, and the water bath temperature was maintained at 70°C. Once all the second metal salt solution had been added to the reactor, the addition of the second precipitant was stopped, and the precipitate was allowed to age at a constant temperature in the reactor for 1 hour to obtain the first precipitate slurry.

[0056] The third metal salt solution and another portion of the first precipitant were then added dropwise to the second reactor in a parallel flow. Throughout the process, the mixture was continuously stirred, and the pH was controlled between 7.5 and 8.5 by adjusting the feed rates of the salt and alkali. The water bath temperature was maintained at 70°C. Once the third metal salt solution had been completely added, the addition of the first precipitant was stopped. Stirring continued for 30 minutes to obtain the second precipitate slurry.

[0057] Finally, the first and second precipitated slurries were mixed and stirred for another 2 hours. Afterward, the mixture was filtered, washed with deionized water, and filtered again. This process was repeated until no Na was detected. + The filter cake was dried and crushed, and the dried material was calcined at 350℃ for 6 hours to decompose it, obtaining calcined powder. The calcined powder was then mixed with 2wt% graphite to form a methanol synthesis catalyst sample C1.

[0058] The mass percentages of sample C1 are: CuO: 62.3%, ZnO: 24.5%, Al2O3: 13.2%.

[0059] Comparative Example 2 Weigh 279.9g Cu(NO3)2·3H2O, 101.40g Zn(NO3)2·6H2O, and 10.77g Mg(NO3)3·6H2O, dissolve them in 1500ml deionized water, and stir until completely dissolved to obtain the first metal salt solution. Weigh 110.30g Al(NO3)3·9H2O and 7.14g Zr(NO3)2·5H2O, dissolve them in 384 mL deionized water, and stir until completely dissolved to obtain the second metal salt solution. Weigh 265.00g Na2CO3, dissolve it in 2500ml deionized water, and stir until completely dissolved to obtain the first precipitant. The first metal salt solution and the first precipitant were added dropwise to the first reactor in a parallel flow. The mixture was stirred continuously throughout the process, and the pH value was controlled between 6.5 and 7.5 by adjusting the feed rates of the salt and alkali. The water bath temperature was maintained at 70°C. Once all the first metal salt solution had been added, the addition of the first precipitant was stopped, yielding the first precipitate slurry.

[0060] The second metal salt solution and another portion of the first precipitant were then added dropwise to the second reactor in a parallel flow. Throughout the process, the mixture was continuously stirred, and the pH value was controlled between 7.5 and 8.5 by adjusting the feed rates of the salt and alkali. The water bath temperature was maintained at 70°C. Once the second metal salt solution had been completely added, the addition of the first precipitant was stopped. Stirring continued for 30 minutes to obtain the second precipitate slurry.

[0061] Finally, the first and second precipitated slurries were mixed and stirred for another 2 hours. Afterward, the mixture was filtered, washed with deionized water, and filtered again. This process was repeated until no Na was detected. + The filter cake was dried and crushed, and the dried material was calcined at 350℃ for 5 hours to decompose it, obtaining calcined powder. The calcined powder was then mixed with 2wt% graphite to form a methanol synthesis catalyst sample C2.

[0062] The mass percentages of sample C2 are: CuO: 62.3%, ZnO: 22.5%, Al2O3: 11.5%, MgO: 1.5%, ZrO2: 2.2%.

[0063] Comparative Example 3 Weigh 279.90g Cu(NO3)2·3H2O, 101.40g Zn(NO3)2·6H2O, and 12.56g Ca(NO3)2·4H2O, dissolve them in 1500ml deionized water, and stir until completely dissolved to obtain the first metal salt solution. Weigh 110.30g Al(NO3)3·9H2O and 8.29g Mn(NO3)2·4H2O, dissolve them in 384 mL deionized water, and stir until completely dissolved to obtain the second metal salt solution. Weigh 265.00g Na2CO3, dissolve it in 2500ml deionized water, and stir until completely dissolved to obtain the first precipitant. The first metal salt solution and the first precipitant were added dropwise to the first reactor in a parallel flow. The mixture was continuously stirred throughout the process, and the pH value was controlled between 6.5 and 7.5 by adjusting the feed rates of the salt and alkali. The water bath temperature was maintained at 70°C. Once all the first metal salt solution had been added, the addition of the first precipitant was stopped, resulting in the first precipitate slurry.

[0064] The second metal salt solution and another portion of the first precipitant were then added dropwise to the second reactor in a parallel flow. Throughout the process, the mixture was continuously stirred, and the pH value was controlled between 7.5 and 8.5 by adjusting the feed rates of the salt and alkali. The water bath temperature was maintained at 70°C. Once all of the salt solution 2 had been added, the addition of the first precipitant was stopped. Stirring continued for 30 minutes to obtain the second precipitate slurry.

[0065] Finally, the first and second precipitated slurries were mixed and stirred for another 2 hours. Afterward, the mixture was filtered, washed with deionized water, and filtered again. This process was repeated until no Na was detected. + The filter cake was dried and crushed, and the dried material was calcined at 350℃ for 5 hours to decompose it, obtaining calcined powder. The calcined powder was then mixed with 2wt% graphite to form the methanol synthesis catalyst sample C3.

[0066] The mass percentages of sample C3 are as follows: CuO: 61.7%, ZnO: 23.0%, Al2O3: 11.5%, CaO: 1.5%, MnO2: 2.3%.

[0067] Comparative Example 4 Weigh 278.52g Cu(NO3)2·3H2O, 80.30g Zn(NO3)2·6H2O, and 10.77g Mg(NO3)3·6H2O, dissolve them in 1500ml deionized water, and stir until completely dissolved to obtain the first metal salt solution. Weigh 22.92g Zn(NO3)2·6H2O and 57.78g Al(NO3)3·9H2O, dissolve them in 230ml deionized water, and stir until completely dissolved to obtain the second metal salt solution. Weigh 57.78g Al(NO3)3·9H2O and 6.95g Ce(NO3)3·6H2O, dissolve them in 154mL deionized water, and stir until completely dissolved to obtain the third metal salt solution. Weigh 265.00g Na2CO3, dissolve it in 2500ml deionized water, and stir until completely dissolved to obtain the first precipitant. Weigh 79.50g Na2CO3 and 10.00g NaOH and dissolve them in 1000ml deionized water, stirring until completely dissolved to obtain the second precipitant; The first metal salt solution and the first precipitant were added dropwise to the first reactor in a parallel flow, with continuous stirring throughout the process. The pH value was controlled between 6.5 and 7.0 by adjusting the feed rates of the salt and alkali, and the water bath temperature was maintained at 70°C. Once all the first metal salt solution had been added, the addition of the first precipitant was stopped. Stirring continued for 1 hour, with the stirrer running continuously. Then, the second metal salt solution was added in the same manner, while the second precipitant was added dropwise. Throughout this process, the pH value was controlled between 9.5 and 10.5 by adjusting the feed rates of the salt and alkali, and the water bath temperature was maintained at 90°C. Once all the second metal salt solution had been added to the reactor, the addition of the second precipitant was stopped, and the precipitate was allowed to age at a constant temperature in the reactor for 2 hours to obtain the first precipitate slurry.

[0068] The third metal salt solution and another portion of the first precipitant were then added dropwise to the second reactor in a parallel flow. Throughout the process, the mixture was continuously stirred, and the pH was controlled between 7.5 and 8.5 by adjusting the feed rates of the salt and alkali. The water bath temperature was maintained at 70°C. Once the third metal salt solution had been completely added, the addition of the first precipitant was stopped. Stirring continued for 30 minutes to obtain the second precipitate slurry.

[0069] Finally, the first and second precipitated slurries were mixed and stirred for another 2 hours. Afterward, the mixture was filtered, washed with deionized water, and filtered again. This process was repeated until no Na was detected. + The filter cake was dried and crushed, and the dried material was calcined at 350℃ for 6 hours to decompose it, obtaining calcined powder. The calcined powder was then mixed with 2wt% graphite to form a methanol synthesis catalyst sample C4.

[0070] The mass percentages of sample C4 are: CuO: 60.8%, ZnO: 23.5%, Al2O3: 11.7%, MgO: 1.5%, CeO2: 2.5%.

[0071] Comparative Example 5 Weigh 279.90g Cu(NO3)2·3H2O and 95.40g Zn(NO3)2·6H2O and dissolve them in 1500ml deionized water, stirring until completely dissolved to obtain the first metal salt solution. Weigh 110.30g Al(NO3)3·9H2O and dissolve it in 384ml deionized water, stirring until completely dissolved to obtain the second metal salt solution. Weigh 265.00g Na2CO3 and dissolve it in 2500ml deionized water, stirring until completely dissolved to obtain the first precipitant. The first metal salt solution and the first precipitant were added dropwise to the first reactor in a parallel flow. The mixture was stirred continuously throughout the process, and the pH value was controlled between 6.5 and 7.5 by adjusting the feed rates of the salt and alkali. The water bath temperature was maintained at 70°C. Once all the first metal salt solution had been added, the addition of the first precipitant was stopped, yielding the first precipitate slurry.

[0072] The second metal salt solution and another portion of the first precipitant were then added dropwise to the second reactor in a parallel flow. Throughout the process, the mixture was continuously stirred, and the pH value was controlled between 7.5 and 8.5 by adjusting the feed rates of the salt and alkali. The water bath temperature was maintained at 70°C. Once the second metal salt solution had been completely added, the addition of the first precipitant was stopped. Stirring continued for 30 minutes to obtain the second precipitate slurry.

[0073] Finally, the first and second precipitated slurries were mixed and stirred for another 2 hours. Afterward, the mixture was filtered, washed with deionized water, and filtered again. This process was repeated until no Na was detected. + The filter cake was dried and crushed, and the dried material was calcined at 350℃ for 5 hours to decompose it, obtaining calcined powder. The calcined powder was then mixed with 2wt% graphite to form the methanol synthesis catalyst sample C5.

[0074] The mass percentages of sample C5 are: CuO: 62.8%, ZnO: 23.5%, and Al2O3: 13.7%.

[0075] Experimental Case 1 The catalyst activity was tested using a fixed-bed high-pressure microreactor. The catalyst samples prepared in Examples 1-3 and Comparative Examples 1-5 were crushed, passed through a 20-50 mesh sieve, and then loaded into a 4 ml container (2 ml catalyst + 2 ml of ceramic rings of equal particle size). Before the activity test, a temperature-programmed reduction was performed under a 5% H2-95% N2 atmosphere. The temperature was increased from room temperature to 170°C and held for 2 hours over 4 hours, followed by a further increase to 220°C and held for another 2 hours. The methanol synthesis reaction conditions were: reaction pressure 5.0 MPa, reaction temperature 235-245°C, and space velocity 10000 h⁻¹. -1 The volumetric composition of the raw gas is: CO = 13.0-14.0%, CO2 = 4.0-5.0%, N2 = 10%, and the remainder is H2.

[0076] Heat resistance test conditions: heat resistance temperature 400℃, heat resistance time 10h, space velocity 3000h⁻¹ -1 Reaction conditions after heat resistance: reaction pressure 5.0 MPa, reaction temperature 235-245℃, space velocity 10000 h⁻¹ -1 Under the above conditions, methanol synthesis was carried out, and the initial CO conversion rate (%) and methanol space-time yield (g·ml) of catalyst samples 1-3 and C1-C5 were determined respectively. -1 ·h -1 ) and its initial CO conversion rate (%) and methanol space yield (g·ml) after heat resistance test -1 ·h -1 The thermal stability of the catalyst was compared by the ratio of the methanol space-time yield after the heat resistance test to the initial methanol space-time yield. The results are shown in Table 1.

[0077] Table 1. Test results of Examples 1-3 and Comparative Examples 1-5

[0078] As shown in Table 1, the catalyst samples 1, 2, and 3 prepared in Examples 1-3 all exhibited superior performance compared to comparative examples C1-C5 in terms of initial CO conversion, initial methanol space-time yield, CO conversion after the heat resistance test, methanol space-time yield after the heat resistance test, and thermal stability (the ratio of methanol space-time yield after the heat resistance test to the initial methanol space-time yield). Among them, sample 2 showed particularly outstanding overall performance, with an initial CO conversion of 83.6% and an initial methanol space-time yield of 1.58 g·ml. -1 ·h -1 After the heat resistance test, the CO conversion rate remained at 80.2%, and the methanol space-time yield after the heat resistance test was 1.42 g·ml. -1 ·h -1 It has a thermal stability of up to 0.90.

[0079] In Comparative Example 1, since neither the active component nor the support underwent doping modification, the dispersion of the active component in the catalyst decreased, and the CuO crystals were prone to agglomeration, resulting in a lower initial CO conversion rate (79.6%) and an lower initial methanol space-time yield (1.48 g·ml⁻¹). -1 ·h -1 The values ​​were all lower than those of the example samples, and the performance degradation was more obvious after the heat resistance test, with a thermal stability of only 0.80.

[0080] Comparative Example 2 did not form a sandwich structure and was prepared using only a single precipitation method. Although MgO and ZrO2 promoters were introduced, the dispersion uniformity of the active component and promoters was poor, resulting in a low initial CO conversion rate (77.7%) and initial methanol space-time yield (1.50 g·ml). -1 ·h -1 The performance was slightly lower than that of the example, and the performance degraded significantly after heat resistance, with a thermal stability of only 0.75, indicating that the introduction method of Zn-O-Al has a significant impact on the catalyst performance.

[0081] Comparative Example 3 also did not form a sandwich structure. CaO and MnO2 were used as additives, although its initial CO conversion (76.2%) and initial methanol space-time yield (1.45 g·ml) were relatively high. -1 ·h -1 The results were similar to those of Comparative Example 2, but the CO conversion rate (69.7%) and methanol space-time yield (1.03 g·ml) were significantly lower after the heat resistance test. -1 ·h -1 The temperature stability of the catalyst decreased further, and the thermal stability (0.71) was also worse, indicating that the choice of additives is equally important for the high-temperature stability of the catalyst.

[0082] Comparative Example 4 attempted to construct a complex structure through multi-step precipitation and pH adjustment with different alkaline solutions. However, due to improper control of process parameters and an excessive number of salt solutions leading to disordered interactions between components, the CO conversion rate (67.8%) and methanol space-time yield (1.12 g·ml) were significantly lower after the heat resistance experiment. -1 ·h -1 The largest decrease was observed in thermal stability (0.74), which did not meet expectations.

[0083] Comparative Example 5, as a base system without any additives, exhibited the lowest performance in all aspects, fully demonstrating that the CuO-ZnO-Al2O3 ternary system, lacking the synergistic effect of additives, struggles to meet the requirements for high activity and high-temperature resistance. In summary, this invention, through optimizing the proportion of active components, introducing specific additives, and employing a stepwise precipitation method to construct a "sandwich" structure, significantly improves the number, dispersion, and structural stability of the catalyst's active centers, thereby demonstrating superior catalytic performance and high-temperature tolerance in the methanol synthesis reaction.

[0084] Experimental Case 2 The catalyst samples 1-3 and C1-C5 prepared in Examples 1-3 and Comparative Examples 1-5 were analyzed by XRD patterns. The results are shown in the figure. Figure 3 .

[0085] As can be seen from the figure, the samples prepared using the method of this invention exhibit characteristic peaks of CuO at 23.5°, 31.5°, and 38.0°. Compared with the comparative examples (C1-C3), the example samples (1-3) show additional diffraction peaks corresponding to ZnAl2O4 (47.5°, 52.5°). This directly proves that the stepwise precipitation method of this invention successfully constructs a phase composition different from that of traditional catalysts, namely the existence of a "Zn-O-Al" intermediate layer. The diffraction peaks of the example samples (especially the peaks near 38.0°) show broadening, which is completely consistent with the description of doping leading to particle refinement and improved dispersibility.

[0086] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A highly active, high-temperature resistant methanol catalyst, characterized in that, The catalyst has a sandwich structure with copper oxide-zinc oxide as the core, zinc-oxygen-aluminum composite oxide as the middle layer, and aluminum oxide as the shell; The catalyst contains doping elements; the doping elements include a first doping element for regulating the active component and a second doping element for modifying the support; The first dopant element is distributed in the core and is selected from at least one of the alkaline earth metals Ca, Mg, and Ba; the second dopant element is distributed in the shell and is selected from at least one of the rare earth metals Ce, La, and Pr or the d-block metals Mn, Zr, and Ti. The catalyst comprises the following components by mass: 52-74 parts copper oxide, 17-27 parts zinc oxide, 9-23 parts aluminum oxide, 0.5-2 parts alkaline earth metal, and 1-5 parts rare earth metal or d-block metal.

2. A method for preparing a highly active, high-temperature resistant methanol catalyst, characterized in that, The preparation of the highly active, high-temperature resistant methanol catalyst according to claim 1 includes the following steps: Prepare at least three different metal salt solutions, which are respectively used to form the core, intermediate layer and shell of the catalyst; By using a stepwise coprecipitation method, under first conditions, a first metal salt solution used to form the core is reacted with a portion of a first precipitant to obtain a core slurry; Under the second condition, a second metal salt solution for forming the intermediate layer and a second precipitant are added to the core slurry and precipitated on the surface of the solid particles of the core slurry to obtain a first precipitated slurry; The third metal salt solution used to form the shell is reacted with another portion of the first precipitant to obtain a second precipitate slurry; The first precipitated slurry and the second precipitated slurry are mixed and then aged. The aged product was subjected to solid-liquid separation, washing, drying, and calcination to obtain the catalyst precursor; The catalyst precursor is shaped to obtain the methanol catalyst.

3. The method for preparing the highly active, high-temperature resistant methanol catalyst according to claim 2, characterized in that, The first precipitant is a carbonate solution; The second precipitant is a mixed solution of carbonate and alkali metal hydroxide.

4. The method for preparing the highly active, high-temperature resistant methanol catalyst according to claim 3, characterized in that, The molar ratio of zinc to aluminum in the second metal salt solution is 1.5-2.5:1; The carbonate solution is a sodium carbonate solution, and the second precipitant is a mixed solution of sodium carbonate and sodium hydroxide; In the second precipitant, the molar ratio of sodium carbonate to sodium hydroxide is 1-3:

1.

5. The method for preparing the highly active, high-temperature resistant methanol catalyst according to claim 2, characterized in that, The first condition includes: a reaction temperature of 60-80℃, a reaction pH value maintained at 6.5-7.5, and an aging time of 1-3 hours; The second condition includes: a reaction temperature of 60-80℃, a reaction pH value maintained at 8.5-9.5, and an aging time of 0.5-2 hours.

6. The method for preparing the highly active, high-temperature resistant methanol catalyst according to claim 2, characterized in that, The roasting temperature is 300-400℃, and the roasting time is 3-6 hours.

7. The method for preparing the highly active, high-temperature resistant methanol catalyst according to claim 2, characterized in that, The molding process involves adding graphite to the calcined catalyst precursor and pressing it into tablets, wherein the amount of graphite added is 1-3 wt% of the total mass of the catalyst.

Citation Information

Patent Citations

  • Modified gamma-alumina support as well as preparation method and application thereof

    CN105582905A

  • Synthesis gas methanol catalyst and preparation method thereof

    CN109289855A

  • Preparation method of high-selectivity methanol synthesis catalyst

    CN117504883A

  • Catalyst for preparing methanol through carbon dioxide hydrogenation and preparation method thereof

    CN120515422A